Marketing public relations strategy for Islamic Hospitals in Bandung City - Dewi, Retasari; Rafli, Zahwa Putri; Anisa, Renata; Yustikasari, Yustikasari; Abdullah, Zulhamri bin (Universitas Padjadjaran, 2025)
Background: The increasing prevalence of hospitals with comparable service offerings has resulted in heightened rivalry within the healthcare sector. This competition prompted three Islamic-based hospitals in Bandung to formulate strategies that integrate marketing public relations (MPR) with Sharia principles while maintaining competitiveness. Few studies on hospital MPRs have investigated the significance of religiosity in public relations techniques. This indicates a requirement for research that comprehends how Islamic hospitals reconcile Islamic ethical precepts with marketing imperatives via public relations methods. Purpose: This study aims to identify and examine MPR techniques employed by Islamic hospitals in Bandung City to align with Islamic ideals. Methods: This study employed a multi-site case study methodology involving three Islamic hospitals in Bandung City: RS Al Islam, RSIA Al Islam, and RS Muhammadiyah Bandung. Data were gathered via restricted contextual observation, semi-structured in-depth interviews, and secondary documentation. Results: The findings of this study indicate that Islamic hospitals predominantly employ pull and pass procedures over push tactics. The push method is implemented selectively to uphold integrity and Islamic beliefs. This study affirms that Islamic hospitals build their image through physical symbols, media, community engagement, and institutional obligations such as certification and accreditation. Conclusion: Islamic hospitals employ MPR methods to sustain competitiveness; nevertheless, these strategies are not exclusively utilized as marketing instruments or for image preservation. They also embody the institutions’ principles and identities, thereby fostering public trust over time. Implications: This research could enhance people’s understanding of MPR, particularly within the healthcare sector and Islamic public relations